2015
DOI: 10.1038/eye.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

Association of histone acetylation at the ACTA2 promoter region with epithelial mesenchymal transition of lens epithelial cells

Abstract: Purpose Epithelial mesenchymal transition (EMT) plays a central role in the development of fibrotic complications of the lens. The current study is designed to check whether EMT of lens epithelial cells (LECs) is regulated by epigenetic modifications and to evaluate the effect of Trichostatin-A (TSA) on the transforming growth factor-β (TGF-β)-induced EMT. Methods Fetal human LECs (FHL124) were treated with TGF-β2 in the presence or absence of TSA. Levels of mRNA, protein, as well as localization of α-smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…Fifteen short tandem repeat (STR) loci plus the gender determining locus, Amelogenin, were amplified using the PowerPlex® 16 HS System from Promega and processed using the ABI Prism® 3100-Avant Genetic Analyzer. Data analyzed using the GeneMapper® v4.0 Software from Applied Biosystems confirmed that the cell line was of a human male origin and showed a 96% match with the reported analysis [42] (Table 1). The cells were cultured in MEM (Life Technologies, Carlsbad, CA) containing 5% FBS (Life Technologies) and gentamycin/L-glutamate (Sigma-Aldrich, St. Louis, MO) and maintained in a humidified incubator at 37 °C containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 54%
“…Fifteen short tandem repeat (STR) loci plus the gender determining locus, Amelogenin, were amplified using the PowerPlex® 16 HS System from Promega and processed using the ABI Prism® 3100-Avant Genetic Analyzer. Data analyzed using the GeneMapper® v4.0 Software from Applied Biosystems confirmed that the cell line was of a human male origin and showed a 96% match with the reported analysis [42] (Table 1). The cells were cultured in MEM (Life Technologies, Carlsbad, CA) containing 5% FBS (Life Technologies) and gentamycin/L-glutamate (Sigma-Aldrich, St. Louis, MO) and maintained in a humidified incubator at 37 °C containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 54%
“…The figure shows phase contrast images of cells treated with 0.5 μM and 1 μM of TSA (labels on left) ±10 ng/ml TGF-β2 (labels above). [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…The 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay was used to determine the viability of LECs after TSA treatment. [ 20 ] Briefly, 7 × 10 3 cells per well were added to 96-well plates and incubated for 24 hours. The cells were treated with a wide range of TSA concentrations (0.1-5 μM) for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations